The role of E3 ubiquitin ligases and deubiquitinases in bladder cancer development and immunotherapy - Wang, Xuemei; Zhang, Ying; Wu, Yao; Cheng, Hongjing; Wang, Xueju (Frontiers in Immunology, 2023)
Bladder cancer is one of the common malignant urothelial tumors. Post-translational modification (PTMs), including ubiquitination, acetylation, methylation, and phosphorylation, have been revealed to participate in bladder cancer initiation and progression. Ubiquitination is the common PTM, which is conducted by E1 ubiquitin-activating enzyme, E2 ubiquitin-conjugating enzyme and E3 ubiquitin-protein ligase. E3 ubiquitin ligases play a key role in bladder oncogenesis and progression and drug resistance in bladder cancer. Therefore, in this review, we summarize current knowledge regarding the functions of E3 ubiquitin ligases in bladder cancer development. Moreover, we provide the evidence of E3 ubiquitin ligases in regulation of immunotherapy in bladder cancer. Furthermore, we mention the multiple compounds that target E3 ubiquitin ligases to improve the therapy efficacy of bladder cancer. We hope our review can stimulate researchers and clinicians to investigate whether and how targeting E3 ubiquitin ligases acts a novel strategy for bladder cancer therapy.